Biocompatible tellurium nanoneedles with long-term stable antibacterial activity for accelerated wound healing. (June 2022) - Huang, Ling; Liu, Meng; Feng, Zhibin; Xu, Xingyi; Chen, Lingling; Ma, Zhijun; Li, Lihua
Abstract: Tellurium (Te) nanomaterials (NMs) have emerged as a new antibacterial candidate to respond to the complex global health challenge of bacterial resistance. Herein, Te nanoneedles (NNs) that act both chemically and physically on bacteria are synthesized by a facile method using Na2 TeO3, urea and glucose. It is found that the prepared Te NNs have a strong affinity to the cell membrane of bacteria and subsequently promote the generation of reactive oxygen species (ROS) in bacteria, resulting in an excellent antibacterial effect toward Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative). What's more, this needle-like morphology also can physically damage the bacterial cell membranes. The Te NNs per se are inert in mammalian cells to produce ROS at a proper concentration, indicating considerable biocompatibility of this material. As a proof-of-concept, the antibacterial Te NNs were used as an anti-inflammatory reagent for promoting bacteria-infected wound healing in vivo, during which Te NNs caused no evident side effects to major organs in mice. Additionally, the antibacterial activity is maintained in the presence of surface oxidation of Te NNs after long-term dispersion in phosphate buffered saline solution. The needle-like Te NMs with long-term antibacterial stability and good biocompatibility have great potential for the treatment of associated infectious diseases. Graphical abstract: Image 1